Upgrading the integration of supercritical coal-fired power plant with post-combustion CO2 capture process through process simulation. (2017) - Liu, Xiaoyan; Yu, Yanmei; Chen, Jian
The purpose of this study is to alleviate the negative effect of post-combustion CO2 capture (PCC) process on the generating efficiency of a 600 MWe supercritical coal-fired power plant (CFPP) through modelling and simulation. Steady state models for a 600 MWe supercritical CFPP and a MEA-based PCC plant with corresponding compression unit were developed and integrated in Aspen Plus. In the two basic cases with steam extracted from different locations, efficiency penalty of 14.48% points and 11.89% points were caused, respectively. Subsequently, four steps were taken to improve the overall performance of the integrated process, which involves: 1) waste heat recovery; 2) throttling loss reduction; 3) capture flowsheet modification and 4) temperature difference narrowing. From the final simulation results, the efficiency penalty is reduced to 8.07% points. This study indicates that appropriate flowsheet modifications for the integrated process can significantly improve the overall energy efficiency.